Back from the undead - Barant, D. D. (New York, N.Y. : St. Martin's Paperbacks, 2012)
FBI profiler Jace Valchek teams up with her former lover, Tanaka, whose family is one of the last samurai clans left in Japan, to infiltrate a child-trafficking ring of pire orphans that is part of a blood-farm operation.